(untitled) (Journal of Governance and Development (JGD), 2021)
Up to date, Non-Revenue Water (NRW) is still a problem in many states. This study is focused on the states of Negeri Sembilan and Johor. A team of Malaysian lecturers from Faculty of Accountancy and Management, Universiti Tunku Abdul Rahman (UTAR), under the Malaysian governmental grant (TRGS 2016-1) are researching how to combat the NRW problem in the states of Negeri Sembilan and Johor. Data were collected through field research and focus group interviews from both Ranhill Water Services Sdn Bhd (Ranhill) and Syarikat Air Negeri Sembilan Sdn Bhd (SAINS). This study also looked into the laws and several legal cases involving non-revenue in Malaysia. Our research questions are what is non-revenue water, what are the institutions governing non-revenue water in Malaysia, what are the legislations and cases of non-revenue water in Malaysia and how do we overcome non-revenue water in Malaysia based on findings from Johor and Negeri Sembilan. From the research have found that the main contributors to NRW in Johor are a leakage in their pipe system and also reservoir overflow. They are now utilizing loggers to detect leakage. It was highlighted that amongst the challenges to combat NRW are the acknowledgement and awareness on the client-side and educating the client on the true situation of the pipe conditions and how to manage the NRW problem. As for SAINS, awareness is the same issue faced by SAINS just like Ranhill in which 80.0% are still more focused towards water supply rather than NRW.